The comparison of the effect of non-pharmacological pain relief and pharmacological analgesia with remifentanil on fear of childbirth and postpartum depression: a randomized controlled clinical trial - Parinaz masroor; Esmat Mehrabi; Roghaiyeh Nourizadeh; Hojjat Pourfathi; Mohammad Asghari-Jafarabadi (BMC, 2024)
Abstract Introduction Childbirth may be associated with psychological, social, and emotional effects and provide the background for women's health or illness throughout their life. This research aimed at comparing the impact of non-pharmacological pain relief and pharmacological analgesia with remifentanil on childbirth fear and postpartum depression. Materials and method This randomized clinical trial with two parallel arms was conducted on 66 women with term pregnancy referred to Taleghani Hospital in Tabriz for vaginal delivery during September 2022 to September 2023. First, all of the eligible participants were selected through Convenience Sampling. Then, they were randomly assigned into two groups of pharmacological analgesia with remifentanil and non-pharmacological analgesia with a ratio of 1:1 using stratified block randomization based on the number of births. Before the intervention, fear of childbirth (FOC) was measured using Delivery Fear Scale (DFS) between 4 and 6 cm cervical dilatation. Pain and fear during labor in dilatation of 8 cm were measured in both groups using VAS and DFS. After delivery, FOC was assessed using Delivery Fear Scale (W DEQ Version B) and postpartum depression using the Edinburgh's postpartum depression scale (EPDS). Significance level was considered 0.05. Mean difference (MD) was compared with Independent T-test and ANCOVA pre and post intervention. Results The mean score of FOC in the non-pharmacological analgesia group was significantly lower than that in the pharmacological analgesia group after the intervention by controlling the effect of the baseline score (MD: -6.33, 95%, Confidence Interval (CI): -12.79 to -0.12, p = 0.04). In the postpartum period, the mean score of FOC in the non-pharmacological analgesia group was significantly lower than that in the pharmacological analgesia group after controlling the effect of the baseline score (MD: -21.89; 95% CI: -35.12 to -8.66; p = 0.002). The mean score of postpartum depression in the non-pharmacological analgesia group was significantly lower than that in the pharmacological analgesia group (MD: -1.93, 95% CI: -3.48 to -0.37, p = 0.01). Trial registration: Iranian Registry of Clinical Trials (IRCT): IRCT20170506033834N10. Date of registration: 05/07/2022 Date of first registration: 05/07/2022. URL: https://www.irct.ir/trial/61030; Date of recruitment start date05/07/2022. Conclusion The study results indicated a reduction in FOC and postpartum depression among parturient women receiving non-pharmacological strategies with active participation in childbirth compared to women receiving pharmacological analgesia. Owing to the possible side effects of pharmacological methods for mother and fetus, non-pharmacological strategies with active participation of the mother in childbirth are recommended to reduce the FOC and postpartum depression.